Antibacterial and antifungal activity of defensins from the Australian paralysis tick, Ixodes holocyclus - Cabezas-Cruz, Alejandro; Tonk, Miray; Bleackley, Mark R; Valdés, James J; Barrero, Roberto A; Hernández-Jarguín, Angélica; Moutailler, Sara; Vilcinskas, Andreas; Richard-Forget, Florence; Anderson, Marilyn A; Rodriguez-Valle, Manuel (Ticks and tick-borne diseases, 2019)
Tick innate immunity involves humoral and cellular responses. Among the humoral effector molecules in ticks are the defensins which are a family of small peptides with a conserved γ-core motif that is crucial for their antimicrobial activity. Defensin families have been identified in several hard and soft tick species. However, little is known about the presence and antimicrobial activity of defensins from the Australian paralysis tick Ixodes holocyclus. In this study the I. holocyclus transcriptome was searched for the presence of defensins. Unique and non-redundant defensin sequences were identified and designated as holosins 1 - 5. The antimicrobial activity of holosins 2 and 3 and of the predicted γ-cores of holosins 1-4 (HoloTickCores 1-4), was assessed using Gram-negative and Gram-positive bacteria as well as the fungus Fusarium graminearum and the yeast Candida albicans. All holosins had molecular features that are conserved in other tick defensins. Furthermore holosins 2 and 3 were very active against the Gram-positive bacteria Staphylococcus aureus and Listeria grayi. Holosins 2 and 3 were also active against F. graminearum and C. albicans and 5 μM of peptide abrogate the growth of these microorganisms. The activity of the synthetic γ-cores was lower than that of the mature defensins apart from HoloTickCore 2 which had activity comparable to mature holosin 2 against the Gram-negative bacterium Escherichia coli. This study reveals the presence of a multigene defensin family in I. holocyclus with wide antimicrobial activity.
Keywords: sekvenční seřazení; Ixodes; proteiny členovců; Ticks; Phylogeny; defensiny; antifungální látky; klíště; antibakteriální látky; zvířata; Arthropod Proteins; Amino Acid Sequence; Antifungal activity; Anti-Bacterial Agents; Antibacterial activity; Antifungal Agents; fylogeneze; transkriptom; Sequence Alignment; Gram-Negative Bacteria; Transcriptome; grampozitivní bakterie; Defensins; Candida albicans; Animals; Gram-Positive Bacteria; Ixodes holocyclus; Austrálie; Australia; gramnegativní bakterie; Fusarium; sekvence aminokyselin